Synthesis of EDTA-Functionalized Silica Coated Nanomagnetite as a Cobalt(II) Ion Adsorbent - Kusumaningrum, Irma Kartika; Arabillah, Zulfikar Wildan; Kusfianti, Anisa Aulia; Munzil, Munzil; Wijaya, Anugrah Ricky (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
This research aims to synthesize silica-coated nanomagnetite EDTA functionalized (Fe3O4@SiO2-EDTA) to characterize its properties and test its ability to bind Co(II) metal ions. This research was carried out in several steps, including Synthesis of nanomagnetite and characterization via SEM, VSM, XRD, and FTIR; (2) Synthesis of nanomagnetite-coated silica (TEOS) and characterization via SEM, VSM, (3) Synthesis and characterization of silica-coated nanomagnetite with EDTA functionalization (Fe3O4@SiO2-EDTA), and characterization was carried out via SEM, VSM, XRD, and FTIR. (4) Adsorption ability test of Fe3O4@SiO2-EDTA as a Co(II) metal ion adsorbent. EDTA-functionalized silica-coated nanomagnetite was successfully synthesized. Confirmation and characterization of the synthesized material was performed on the basis of the FTIR spectrum band at wavenumber 687 cm-1, which confirmed the formation of magnetite, whereas the absorption band at wavenumber 1092 cm-1 confirmed the formation of a silica coating, and the peak at wavenumber 1617 cm-1 confirmed EDTA functionalization in the material. The peak of the XRD chromatogram is shown in XRD pattern 2, which confirms nanomagnetite, and in silica-coated nanomagnetite, the resulting characteristic peak is the same as the characteristic peak in Fe3O4 except in region 24, which confirms the presence of the silica coating. The magnetization of nanomagnetite before coating was 57 emu/g and that after coating was 48 emu/g. The maximum adsorption ability of the synthesized material for Co(II) ions was 0.1336 mg/g.